Modeling the Dependence of Power Diode on Temperature and Radiation - S.M. El-Ghanam; A.M. Abd El-Maksood; F.A.S. Soliman (Institute of Advanced Engineering and Science, 2015)
A theoretical study had been carried out on the effect of radiation on the electrical properties of silicon power diodes. Computer program